The Effect Of Social Media Communication And Service Quality On Behavioral Intentions Mediated By Consumer Satisfaction And Brand Love And Self-Esteem As Moderators In Surabaya Coffee Shop - Gilbert Billy Rivaldo Matahurila; Nanis Susanti; Estik Hari Prastiwi (International Journal of Economics, Business and Innovation Research, 2025)
The development of technology and the internet has brought significant changes in the way people interact, communicate, and make purchasing decisions. In Surabaya, as one of the big cities in Indonesia, this coffee shop phenomenon is very visible. Many new coffee shops have sprung up, each with different concepts and target markets. Competition between coffee shops is getting tighter, encouraging them to continue to innovate and improve their marketing strategies, especially through social media and collaboration with influencers. The purpose of this study was to determine the effect of Social Media Communication, Service Quality, Consumer Satisfaction, Brand Love, Self-Esteem on Behavioral Intentions of Coffeeshop consumers in Surabaya. The research method used in this study is a quantitative method with data collection through a questionnaire using a Likert scale with a survey that has been conducted on 100 respondents with the criteria of visitors and have visited a coffee shop in Surabaya. The data obtained were then analyzed using SEM analysis using PLS 4.0 software. Based on the results of testing as many as eight hypotheses out of fourteen hypotheses accepted.